2016
DOI: 10.1159/000444334
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and White Matter Changes Associated with Renal Transplantation

Abstract: Background: End-stage renal disease (ESRD) is a disease with an aging population and a high prevalence of cognitive impairment affecting quality of life, health care costs and mortality. Structural changes in the brain with decreased white matter integrity have been observed in ESRD. Understanding the changes in cognition and associated changes in brain structure after renal transplantation can help define the mechanisms underlying cognitive impairment in ESRD. Methods: We conducted a prospective, observationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…Notably, this measured improvement in cognition was sustained at 1 year although not exceeding the improvements noted at 3 months post-transplant [9] . Furthermore, the findings noted on DTI could not have been explained by conventional MRI findings [9] . The reader is also directed to a recent study on kidney transplant recipients reported by Zhang et al [10] where the authors examined brain imaging and the default mode network (DMN) that subserves core processes of human cognition such as cognitive and emotional processing, monitoring of the surrounding environment and mind wandering.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…Notably, this measured improvement in cognition was sustained at 1 year although not exceeding the improvements noted at 3 months post-transplant [9] . Furthermore, the findings noted on DTI could not have been explained by conventional MRI findings [9] . The reader is also directed to a recent study on kidney transplant recipients reported by Zhang et al [10] where the authors examined brain imaging and the default mode network (DMN) that subserves core processes of human cognition such as cognitive and emotional processing, monitoring of the surrounding environment and mind wandering.…”
mentioning
confidence: 75%
“…Neuropsychologic parameters of memory and executive function improved significantly post-transplantation. These improvements in neuropsychologic tests were paralleled by significant improvements in the DTI metrics, FA and MD in tracts connecting areas associated with memory and executive function, that is, the corpus callosum, cingulate gyrus, forceps minor and forceps major [9] . Notably, this measured improvement in cognition was sustained at 1 year although not exceeding the improvements noted at 3 months post-transplant [9] .…”
mentioning
confidence: 88%
See 3 more Smart Citations